ON SOME ISSUES OF THE MILITARY AND POLITICAL HISTORY OF ABKHAZIA (1989-1999) - Avidzba, A F; Hasba, A S; Osmaev, A D; Lebedev, V S (History, Archeology and Ethnography of the Caucasus, 2016)
The article covers several aspects of the military and political history of Abkhazia in 1989–1999. The authors analyze the conflicts between Georgia and Abkhazia at the end of the 80s of the 20th century, reveal the main problems of confrontation between the leaders of the two republics, present the major military operations, and study the problem of refugees. The article presents V.Ardzinba’s role in solution of the problem of the political status of Abkhazia. International contacts of the leaders of Abkhazia, the role of other countries and organizations in resolving the political and military conflict in the Caucasus have been studied. The authors also analyze the elections, held in Abkhazia within the period under review, and their results, and note the significance of the adoption of the Constitution of Abkhazia, which proclaimed it an independent state.